Development of fermented chestnut with Bacillus natto: Functional and sensory properties. (April 2020) - Dong, Ming-Zhu; An, Juan-Yan; Wang, Li-Tao; Fan, Xiao-Hong; Lv, Mu-Jie; Zhu, Ya-Wei; Chang, Yuan-Hang; Meng, Dong; Yang, Qing; Fu, Yu-Jie
Graphical abstract: Highlights: A healthy and beneficial Bacillus natto was applied for chestnut fermentation. Efficient contents of active ingredients from natto-chestnut were achieved. Natto-chestnut possessed excellent fibrinolytic, antioxidant and hypoglycemic activities. Abstract: Food fermentation can improve food nutritional value and sensory performance, it is considered as an ecofriendly bioprocessing technology. In this work, a fermented natto chestnut food was firstly developed and its active ingredients and functional properties were systematically studied. Through systematic experimental screening, including a single factor experiment and Box-Behnken design, the fermentation parameters of chestnut were optimized and selected. Under the optimal fermentation conditions, fermentation time 56 h, temperature 38 ℃ and 5% inoculum concentration, the fibrinolytic activity of the natto-chestnut reached 6479 IU/g. Meanwhile, higher antioxidant activity of the natto-chestnut was obtained due to the increased contents of total phenolic, total flavonoid and VC. In addition, α-glucosidase inhibition activity was also improved in the natto-chestnut. These results indicated that fermented chestnut could be a new dietary supplement with higher quality and better activities for people′s health.